Pengaruh Penerapan Model Pembelajaran Two Stay Two Stray (TSTS) Terhadap Hasil Belajar PAI Peserta Didik di Kelas V UPT SDN 16 Pinrang Kec. Watang Sawitto Kab. Pinrang - Nur Ria Anggraeni; Usman; Syamsuddin (Prodi PGMI IAI Sahid, 2023)
This study aims to describe the application the two stay two stray learning model in PAI class V UPT SDN 16 Pinrang Kec. Watang Sawitto, describes the PAI learning outcomes of students class V UPT SDN 16 Pinrang Kec. Watang Sawitto, and analyzed the effect the application of the two stay two stray learning model on the PAI learning outcomes of students class V UPT SDN 16 Pinrang Kec. Watang Sawitto. This research iquantitative research, using the 'ex post facto' method. The research subjects were students at UPT SDN 16 Pinrang Kec. Watang Sawiitto with a total of 30 of 92 students taken by purposive sampling technique. Techniques collecting data through closed questionnaires and documentation. Data analysis used descriptive analysis and inferential analysis. Based on the results of the analysis, it was found the application the two stay two stray learning model on PAI subjects in class V UPT SDN 16 Pinrang Kec. Watang Sawitto is in the medium category, which is 60%, PAI learning outcomes students class V UPT SDN 16 Pinrang Kec. Watang Sawitto is in the medium category, namely 50%, and there no significant effect of the application the two stay two stray learning model on the PAI learning outcomes of students class V UPT SDN 16 Pinrang Kec. Watang Sawitto. This can proven the t-test which gets a t-count 0.790 < t-table 2.048, and a significant value of 0.436> 0.05. while the amount contribution only 2.2% and the remaining 97.8% is influenced other factors that are not this study. Keywoards : Two Stay Two Stray, Learning Outcome